Electrosynthesis and characterization of an electrochromic material from poly(1, 6‐bis(2‐thienyl)pyrene) and its application in electrochromic device. Issue 2 (26th August 2013) - Cheng, Xinfeng; Fu, Yunzhi; Zhao, Jinsheng; Zhang, Yucang
ABSTRACT Electrochemical polymerization of 1, 6‐bis(2‐thienyl)pyrene (BTP) could be achieved in acetonitrile/dichloromethane (ACN/DCM) (1:1, by volume) solution containing sodium perchlorate (NaClO4) as a supporting electrolyte. The resulting polymer poly(1, 6‐bis(2‐thienyl)pyrene) (PBTP) were characterized by cyclic voltammetry, UV–vis spectroscopy, and scanning electron microscopy. The resulting polymeric film has distinct electrochromic properties and exhibits three different colors under various potentials. Moreover, the PBTP film showed reasonable optical contrast (DT %) at 700 nm is found to be 29% and satisfactory response time is measured as 1.3 s. An electrochromic device (ECD) based on PBTP and poly(3, 4‐ethylenedioxythiophene) was also constructed and characterized. This ECD has these qualities: quick switching time, reasonable contrast, and good optical memories and redox stability. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 39770.